Preparation of three-dimensional matrices of human gingival tissue and comparison of induction of mesenchymal and blastema stem cell behaviors in prepared scaffolds - Zhao, Jing; Liu, Rui; Zhu, Jing; Chen, Shulan; Liu, Jianxin; Xu, Ling (Cellular and Molecular Biology, 2022)
This study aimed to compare the behavior of rat bone marrow mesenchymal stem cells and rabbit auricle blastema cells implanted in non-cellular gingival tissue scaffold of human. In this regard, the tissues obtained from gingival surgeries in the dental clinic were de-cellulated using two detergents of sodium dodecyl sulfate and triton 100-X. After washing and sterilization, they were used as a scaffold for culture with bone marrow mesenchymal stem cells of rats. Using light and electron microscopy, these scaffolds were examined before and after 1, 2, and 4 weeks of cell culture. Also, the prepared three-dimensional scaffold was placed in the blastema ring obtained from the rabbit earlobe punch. The samples were evaluated 1, 2, and 4 weeks after culture based on histology techniques. The results showed that the study of scaffolds by electron microscopy showed preserving the epithelium matrix and the collagen fibers in the tissue. Structures similar to the epithelium were created in both samples. In addition, induction of cellular secretion was observed in scaffold cells migrating to the scaffold. In general, scaffolds made from human gums can be a good platform for studying cellular behaviors. Of course, further experiments to determine the nature of differentiated cells can help advance our knowledge of matrix cell interactions.